The construction of meaning in Davao City anti-smoking billboards a semiotic study - Apit, Krupska Lenina M.
In November 2002, the Davao City Council passed the Comprehensive Anti-smoking Ordinance No. 043-02. In less than five years, the law has already had some noteworthy accomplishments: the arrest of 5,265 violators, the support and cooperation of 64,000 business establishments, and the removal of all tobacco billboards and signs in the city leaving behind the no-longer-rivaled anti-smoking billboards and signs of the campaign (?WHO Eyes Davao?, 2007). In the mid 2007, at the height of WHO's call to ban smoking, the campaign especially the billboards, gained media attention, support and participation due to the above-cited achievements of the campaign in the city. Interested by the anti-smoking billboards' s accomplishments in getting the attention of a lot of people and sectors, this study used Barthes' Visual Semiotics to analyze the visual make up of billboards and identify the meanings of the text messages and graphics, in addition to the values that the billboards promote in order to challenge the ?sophisticated? lifestyle being sold by their rival, the tobacco billboards.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts